THE EFFECTIVENESS OF HIGH-INTENSITY INTERVAL TRAINING (HIIT) ON CARDIOVASCULAR FITNESS IN YOUTH ATHLETES - Shukla, Tushar Dhar (ShodhKosh: Journal of Visual and Performing Arts, 2021)
This study explores how High-Intensity Interval Training (HIIT) compares to traditional endurance training in improving cardiovascular fitness among youth athletes. By examining key performance metrics such as VO2 max, heart rate variability, and recovery times, alongside health indicators like body composition and blood pressure, this research aims to highlight the benefits and potential drawbacks of incorporating HIIT into training programs for young athletes. The results could influence the optimization of training strategies and enhance athletic performance in youth.